The incidence of injury in elite junior Australian Rules Football and correlation with screening findings and training loads: A pilot study - Dunsford, A.; Magarey, M.; Chalmers, S.; Boesch, E. (Journal of Science and Medicine in Sport, 2011)
Introduction: The injury rates in Australian Rules Football (ARF) are well documented at the elite adult level but research in junior level elite athletes is still in its early stages. Furthermore, preliminary research has been conducted into the correlation between injury rates and musculoskeletal and fitness screening characteristics of these players but little research has been completed investigating the correlation between injury rates and training load in junior elite athletes. The aim of this pilot study was to establish baseline data pertaining to the South Australian National Football League (SANFL) Under 18 players participating in the South Australian team which competed in the ARF National Championships in 2010. These data were collected in conjunction with a larger research project undertaken by the University of South Australia, investigating injury prevalence in junior ARF in South Australia. Methodology: Data were collected regarding fitness and musculoskeletal screening results for the State squad players. Data were also collected on all injuries which occurred during the course of the National Championships program (two months). Formal reporting was not performed as this was a pilot study to gauge the usefulness of these data. Informal reporting of all injuries was completed, including those injuries which resulted in missed games (to correlate with other studies in this area) and missed training sessions (which is more relevant to this subject group). Results: Forty players from nine participating SANFL clubs were tracked through the National Championships program. These players consistently performed well in the fitness testing conducted by the SANFL prior to the program. Only two of these players demonstrated sound musculoskeletal screening test results, with twenty-seven having abnormal findings. Of this latter group, twenty-two reported injuries during the program. Discussion and Conclusion: The injury rates in the state squad were high and there was some positive correlation with adverse musculoskeletal screening findings. The effect of playing load on these players is difficult to measure but worthy of further consideration. The findings of this pilot study highlight an area requiring further research, which will be ongoing with this playing group.